Is uncontrolled psoriasis a risk factor for cardiovascular disease?. Issue 1 (January 2017) - Mott, Timothy; Vargas, Marcel; Lessmann, Brett
Abstract : EVIDENCE‐BASED ANSWER : A patient with severe psoriasis is at increased risk of developing and dying from cardiovascular disease (CVD) (SOR: B, meta‐analyses of cohort studies with significant heterogeneity).